Exploration and Characterization of Host Trees and Orchid Epiphyte Zones in Lore Lindu National Park, Central Sulawesi - Nasrun, Muhammad Syaifuddin; Gailea, Rosmaniar; Aminah, Sitti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Host trees are vital for the survival of epiphytic orchids, providing necessary light and air circulation for optimal growth. Large trees with tall canopies contribute to the broader distribution of epiphytic orchids in forest areas. This research aimed to identify the characteristics of orchid host tree species in Lore Lindu National Park, considering both elevation zones and orchid growth zones. The research was conducted at various locations within the park, employing the field exploration survey method (cruise method). This method involved comprehensive exploration at each research site and establishing observation paths along pioneer lines, mainly where orchid host trees were found. The findings indicate the presence of 20 types of orchid host trees and 35 species of epiphytic orchids. The basal branching zone (Zone 3) was the most populated by epiphytic orchids on host trees, and the lowland forest was the elevation zone where most orchid host trees were found in Lore Lindu National Park, Central Sulawesi. Keywords: host trees, Lore Lindu National Park, orchids, zone distribution